2004
DOI: 10.1007/s00402-004-0714-1
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic reduction and suture fixation of displaced tibial intercondylar eminence fractures in adults

Abstract: Arthroscopy-assisted screw fixation is more stable, and it allows early exercise. However, the fragment must be large enough to be fixed with a screw. Comminuted or small fragments present limitations for screw fixation techniques. We used the non-absorbable intraligmentous suture to pull down the fragment regardless of small size or comminuted status. The technique is simple and provided secure fixation without damage to the ACL insertion. A second operation is not required to remove the hardware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Fractures of the tibial intercondylar eminence are classified into three types by Meyers and Mckeever: type I, minimal or non-displaced; type II, partially displaced or hinged fracture; and type III, completely displaced. Zaricznyj adds a comminuted fracture as type IV [2,4]. Although tibial intercondylar eminence fractures are rare, many authors have reported different treatments and surgical repairs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fractures of the tibial intercondylar eminence are classified into three types by Meyers and Mckeever: type I, minimal or non-displaced; type II, partially displaced or hinged fracture; and type III, completely displaced. Zaricznyj adds a comminuted fracture as type IV [2,4]. Although tibial intercondylar eminence fractures are rare, many authors have reported different treatments and surgical repairs.…”
Section: Discussionmentioning
confidence: 97%
“…Most authors agree that conservative treatment is sufficient for non-displaced fractures. Displaced fractures are considered an indication for surgery [4]. This is because they may result in non-union, malunion or loss of knee extension [3,5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimally displaced fractures (type 1, and ,2 mm type 2) can be treated conservatively in a long leg cast approximately 10-20 degrees flexion for the anterior 9,10 and 40 degrees flexion for posterior fractures. 11 Type 2 fractures with severe displacement and all type 3 fractures require surgical fixation. Both open and arthroscopic treatments have been well documented in literature with good results described.…”
Section: Introductionmentioning
confidence: 99%
“…Besides several types of different screws [5,28,30,34], wires [26] and folded surgical steels [7] sutures [3,19,21,35] were used.…”
Section: Introductionmentioning
confidence: 99%